SHULLUPACANGA: THE ARCHAEOLOGICAL RECORD OF A CEMETERY WITH PICTOGRAPHS ON THE HILL SAN CRISTOBAL DE CHIQUIÁN - Alcalde Gonzales, Javier l. (2004)
The San Cristobal's Shullupacanga hill, forros an outstanding landscape environment, it is placed on Chiquian's proximities, on the front strip of Aija. The Shullupacanga presents itself as a referent of prehispanic occupations with relevant characteristics for populational, funerary and symbolic studies. This site is placed on the middle and high hill's slope. Even though researchers have recovered information about an associated pictographs cemetery, there are no related studies from the region; therefore the information is not suitable for generalization. The follo wing article widely depicts the recovered data and, furthermore, proposes a debate regarding the implications that this kind of information could bring in order to understand the social relations which formally express this activities on the landscape.